Administering Shingles Vaccine Prior to the Initiation of Biologics Therapy: A Systematic Review - Ryan, Alicia; Soo, Alex; O’Rourke, Niall; Nasrudin, Ayub; Khan, Dan; Lafferty, Fiona; Kelly, James; Byrne, Nicola; Semenov, Serhiy (Trinity Student Medical Journal, 2024)
Background: Shingles, also known as herpes zoster, is a viral infection caused by the varicella-zoster virus. The classic feature is a painful dermatomal rash. Although the disease is often self-limiting, complications such as postherpetic neuralgia can cause long-lasting morbidity. Patients who are immunosuppressed are more susceptible to developing shingles. The purpose of this paper is to systematically review the evidence for prophylactic use of the shingles vaccine prior to initiating biological therapy. Objectives: To evaluate the evidence for shingles vaccine prophylaxis prior to initiating biologics therapy. Methods: We performed a comprehensive Boolean search of PubMed and EMBASE from January 2000 to October 2019 for the following terms: prophylaxis, prior, shingles vaccine, varicella-zoster, infliximab, biological therapy, and guidelines. Eligible studies met the following criteria: published in English since 2000, used any shingles vaccine type and dose; and involved both vaccine monotherapy and autoimmune disease biological therapy. Randomised controlled trials, meta-analyses, and systematic reviews were included. Duplicate studies were excluded, as well as non-English papers. Results: 32 studies met the search criteria, of which 8 were selected for the literature review. All studies had generally differing conclusions as to whether shingles vaccination in autoimmune patients undertaking biologic therapy was safe and effective. Conclusions: Patients with autoimmune diseases should be considered for the herpes zoster vaccine prior to initiating biological therapy. Our findings support the use of the live attenuated vaccine, Zostavax, or the non-live vaccine, Shingrix. However, further research is required to evaluate specific autoimmune conditions and specific biological agents with a view to the formulation of national clinical guidelines on the use of the herpes zoster vaccine in the immunocompromised.